The Relaxant Effect of Nitric Oxide Donor on the Contractile Activity of Ileal: Role of Cgmp and Potassium Channels - Al-Habib, Omar Abdul Majeed (Science Journal of University of Zakho, 2013)
Nitric oxide (NO) is a small molecule of endogenous gases and has important physiological functions. It is well known that NO is an inhibitory action of gastrointestinal smooth muscle cells. The aim of this study was to determine the role of cyclic guanosine monophosphate (cGMP) and potassium (K+) channels in relaxation induced by NO of ileal smooth muscles. Sodium nitroprusside (SNP) at doses between (1X10-6to 3X10-4 M) showed more potent relaxant effect in acetylcholine (ACh) (10-5M) than potassium chloride (KCl) (60mM) induced ileal smooth muscle contractions. Before precontraction by ACh, the segments of ileum was incubated for (20) minutes with various blockers such as Methylene blue (MB), Glibenclamide (GLIB), 4-aminopyridine (4-AP), Barium Chloride (BaCl2) and Tetraethylammonium (TEA). In the presence of MB (3mM), 4-AP (1mM), BaCl2 (1mM) and TEA (1mM) significantly inhibited SNP induced relaxation, while GLIB (10-5M) was not able to affect the response to SNP. These results suggested that NO play an important role in the relaxation of ileal, and these effects are mediated via cGMP, voltage-dependent (KV), inward rectifier (KIR) and Ca+2-dependent (KCa) channels.